PENGARUH PENERAPAN E-FILING, DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Ria A. Apriyani; Selfesina Samadara; Munawar Munawar (JAKA - Jurnal Jurusan Akuntasi, 2019)
This study aims to determine: (1) The effect of e-filing application on Taxpayer Compliance in Atambua Tax Office. (2) Taxpayer Awareness of Taxpayer Compliance in Atambua KPP. (3) Effect of e-filing application and Taxpayer Awareness on Taxpayer Compliance in Atambua KPP. The population in this study are taxpayers who are registered as e-filing users at Atambua Tax Office. The sample used in this study were 100 respondents. The data in this study were obtained primarily through a questionnaire (questionnaire). The questionnaire was tested for validity and reliability before the study. The classic assumption tests used are normality test, linearity test, multicollinearity test and heteroscedasticity test. The hypothesis test used is multiple linear regression analysis and t test. The results of this study indicate that (1) The application of e-filing has a positive and significant effect on Taxpayer Compliance in Atambua Tax Office. This is indicated by the coefficient of determination 0.454 which means that the application of e-filing affects taxpayer compliance by 45.4%. (2) The level of understanding of taxation has a positive and significant effect on taxpayer compliance in KPP Pratama Atambua. This is indicated by the coefficient of determination of 0.444 which means the level of understanding of taxation affects taxpayer compliance by 44.4%. (3) Taxpayer awareness has a positive and significant effect on taxpayer compliance in Atambua Tax Office. This is indicated by the coefficient of determination 0.621 means that taxpayer awareness affects taxpayer compliance by 62.1%. (4) The application of e-filing, the level of understanding of taxation and the awareness of taxpayers has a positive and significant effect on taxpayer compliance in KPP Pratama Atambua. This is evidenced by the calculated F value greater than F table that is 59,820> 3.94.